Penataan Permukiman Di Kawasan Kampung Seng Kota Blitar - Agus Gholib (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
Arrangement of Slum in a dense residential neighborhood that tends to be slum must fulfill basic principles. First, legalization of ownership status on land and housing sites, Second, provision or improvement of technical services, such as clean water, waste and management of liquid waste, sanitation, electricity, road sidewalks, street lighting. Third, provision or improvement of social infrastructure such as schools, clinics, community centers, playgrounds, green areas. Fourth, the improvement of the physical environment, including the rehabilitation / improvement of Ineligible Houses. Fifth, if deemed necessary, the construction of new housing units is included in the up-grading scheme. Sixth, a redesign of the settlement development plan, including the harmony of buildings and road patterns in accordance with infrastructure needs. Seventh, a change in the policy or regulatory framework that is more in line with the needs and opportunities available to the urban community. However, the involvement of people who live in slum areas, from the planning process to the implementation of the arrangement and improvement of the quality of slum areas, is a must. So that in determining the priority of community activities will feel part of the improvement and development in the region. From the participation and empowerment, there will be a response from the residents' expectations of the living conditions in accordance with their needs and increased comfort. For this reason, the paradigm from development to empowerment of the development and construction of settlements, requires the comfort of living to be a priority that is taken into consideration in the sustainable arrangement of settlements. Criteria for the comfort of living will be the standard of success in evaluating the results of structuring and improving the quality of slums. The success of the physical arrangement of settlements is not a benchmark for the usefulness and sustainability of an area, but a process of survival that will have a positive impact on changes in the quality of life for people who live in Kampung Seng Area Kerantil Settlements